Spillover Effects from Greek Sovereign Bonds : Evidence from Asia Pacific Banking Portfolios - Lim, Kok Tiong (2016)
The European Crisis that originated from Greece then its spillover to Portugal, Spain, Cyrus, Italy and Ireland, and finally transforming into the European crisis we know today. It was claimed that the fire broke loose with the spark from U.S. subprime crisis that resulted in a credit crunch, and the aforementioned European countries that were heavily indebted, where their debts are 100% more than their respective GDPs failed to secure credit lifelines to service their debts. The domino effect is history, and in fact the crisis had just crossed its 5 years milestone while we are researching on its spillover effect. The trigger point of research interest is that the crisis does not seem to go away anytime soon. Greece, who was claimed to be the epicenter of the crisis, is under the limelight again to be the first developed nation to default on its financial obligation, and the first country to be kicked out of European Union (EU). In July 2015, the development in Greece had spread like wildfire across the globe and indirectly forcing policy makers to appear before the media to comment on its implication to their respective economy. While “Grexit” remains the sole interest of EU, the concerns on credit default effect are beyond boundaries. The debates revolve around key stakeholders from Greece, German, France, IMF and ECB, while the rest of the EU countries’ involvement are minimal to casting their votes on the bailout decisions. The development also caught the attention from Asia pacific countries, which on their own account also experienced multiple crises from the 1997 Asia financial crisis, followed by the U.S. Subprime Crisis, and potentially the current European Crisis. People are nervous and policy makers are making their rounds to address their concerns, hopefully genuinely. While earlier research papers emphasized mainly on European region found that the spillover from Greece is significant on its peer countries, but recent papers discovered that effect of mitigation have managed to isolate and contain Greece’s spillover effect from neighboring countries. However, the spillover effect from Greece to Asia pacific countries are less than a handful and the estimation window emphasize mainly on pre-crisis and immediately in 2010, while the findings from the earlier papers indicated that there is no evidence of spillover from Greece on Asia pacific countries. We reckon that the 5 years milestone had ample of room for development and suspect that the spillover effect was not stagnant in 2010 alone. Having these in mind, our paper focuses on the current estimation window to reflect the revival of Greece crisis from January 2014 to August 2015 using daily data of the bank portfolios from six sample countries in Asia Pacific : Australia, China, Japan, Singapore, South Korea, and Taiwan. We employed GARCH regression model to mitigate heteroscedasticity to generate the event-‐induced volatility for the respective banking portfolios. While our regression estimates found to be consistent with earlier research that our sample countries are insulated from Greek crisis, our literature review indicated that the sample countries are indeed vulnerable to external shocks, at least from specific countries with high correlation on its debts and bilateral trades.